CHI 98 Conference Summary on Human Factors in Computing Systems 1998
DOI: 10.1145/286498.286828
|View full text |Cite
|
Sign up to set email alerts
|

Diaries as family communication tools

Abstract: The modem lifestyle is characterised by its complexity and speed. There is an extra layer of complexity for families where both parents are trying to balance conflicting demands of work and family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Research on SMS and the home environment is beginning to emerge, though. Various user studies have highlighted the importance of both text messaging and home-centric display artefacts in the management of everyday family life [4,6], but technologies building on this research seem few.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on SMS and the home environment is beginning to emerge, though. Various user studies have highlighted the importance of both text messaging and home-centric display artefacts in the management of everyday family life [4,6], but technologies building on this research seem few.…”
Section: Related Workmentioning
confidence: 99%
“…The scenario we had in mind was a person messaging to their family, in the home. This domain appealed since prior studies had shown that micromanagement is an important function of SMS, and family life entails a great deal of micro-management [4,5,6].…”
Section: Introductionmentioning
confidence: 99%